Riwāyāt al-Qirā'āt al-Qur'āniyyah fī Kutub al-Ḥadīṡ Unmūżajan: Riwāyat al-Ḥadīṡ min al-Syafāhiyyat ilā al-Kitābiyyat: [Narrations of Qirā'āt in Selected Hadith Literature: The Transmission of Hadith from the Oral World into the Written Word] - Abdul Jalil (UIN Sunan Kalijaga Yogyakarta, 2021)
The narrators have tried to convey the hadith, its accompanying physical expression, and its reading methods to the listener directly in oral communication. Thus, these learning transmission methods shifted from the oral world to textual word, henceforth it made the narrators rephrase the verbal utterances into written phrases, such as “one separates the fingers”, “his/her voice amplified” and others. The problem is, written expressions might not completely transcribe spoken language, more specifically for the transmitting narrators of the reading methods of the Quranic verses (qirā’at āyāt al-Qur’ān). This article focuses to illustrate forms of narration on the Quranic reading methods in written expressions and the complementary explanations detailed by the narrators. The results appear that some of the narrations on the variety of reading methods of the Qur’an in some Hadith literature required detailed information, such as mentioning the letters of the Arabic letters and how to read specific phrases and punctuation. These additions clarify the variety of the Quranic reading methods hence such utilitarian information is beneficial for the narrations in the mediated world.